Constituents and Metabolites of a French Oak Wood Extract (Robuvit®) in Serum and Blood Cell Samples of Women Undergoing Hysterectomy - Volpp, Linda; Ferianec, Vladimír; Ježovičová, Miriam; Ďuračková, Zdeňka; Scherf-Clavel, Oliver; Högger, Petra (Frontiers in Pharmacology, 2020)
Ellagitannins are signature constituents of oak wood and their consumption has been associated with various health benefits. In vivo, they undergo metabolic degradation including gut microbial metabolism yielding urolithins. Only limited data is available about compounds being present in blood after intake of an extract from French oak wood, Robuvit®. In the course of a randomized, double-blind, controlled clinical investigation, 66 patients undergoing hysterectomy received placebo or 300 mg Robuvit® per day before and over eight weeks after surgery. Serum and blood cell samples were analyzed by LC-ESI-MS/MS. The number of urolithin producers and the urolithin levels increased after intake of Robuvit®. In serum samples, the median concentration of urolithin A was 14.0 ng/mL (interquartile range (IQR) 57.4) after 8 weeks. Urolithin B was determined at 22.3 ng/mL (IQR 12.6), urolithin C at 2.66 ng/mL (IQR 2.08). In blood cells, lower concentrations and only urolithins A and B were detected. A statistically significant association of lower post-surgical pain scores with metabotype A was detected (p< 0.05). To conclude, supplementation with French oak wood extract raised urolithin generation in patients and suggested health advantages for urolithin-producers.